(untitled) (SJ Ophthalmology Africa, 2026)
Background: Corrective glasses are essential optical instruments consisting of a frame that holds a pair of lenses to correct refractive errors, including myopia, hyperopia, astigmatism, and presbyopia. The study aims to establish information related to factors regarding adherence to the use of corrective glasses among patients with refractive errors in Jinja city. Methodology: The study used a cross-sectional study design to collect quantitative data, where 56 respondents were chosen by probability sampling. Data was analysed manually using a scientific calculator, and tabulations were made to establish the relationships between variables. The results were presented in figures, tables, and statements. Results: Of a total of 56 respondents, 18(32.2%) were aged between 46-60 ,33(58.9%) were female, 27(48.2%) had tertiary education and 26(46.4%) employed. 18(32.1%) of the respondents had limited information on the benefits of corrective glass adherence, and 43(76.8%) believed they should be worn some of the time.18(32.1%) respondents found glasses uncomfortable to wear and 20(35.7%) believed that glasses would weaken their eye sight. Majority 32.1% had a neutral understanding, 25.0% understood the benefits well, 17.9% understood the benefits very well, 17.9% who had a poor understanding of the benefits, and l7.1% who had no understanding of the benefits of wearing corrective glasses. The majority (57.1%) know how to care for their corrective glasses. 76.8% believed that corrective glasses should only be worn some of the time, compared to (23.2%) who believed that they should be worn all the time Conclusions: There is limited patient information on adherence to the use of corrective glasses and the benefits of consistently wearing glasses. Recommendations : There’s a need for patients to use their glasses as instructed by the health workers, and to make it a habit to wear them consistently in order to avoid further deterioration in vision.